Self-assembly of phospholipids on flat supports - Mhashal, Anil R.; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
The current study deals with the self-assembly of phospholipids on flat supports using the Martini coarse grain model. We reported here the effect of the hydrophilic and hydrophobic nature of the solid supports on the lipid self-assembly. The hydrophilic and hydrophobic supports were modeled on the basis of water droplet simulations. The present work addresses the self-assembly mechanism of lipids on eight different supports with different strengths of hydrophilicity and hydrophobicity. We demonstrated how interplay between the interactions of lipid and water with the support can guide the lipid self-assembly process. Thereafter, we calculated the energetics of the components of the system to quantify the competitions between water and a lipid head-group with hydrophilic supports. Finally, the properties of the self-assembled bilayers were also analyzed and reported here.